PENGARUH BUDAYA ORGANISASI DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA PT. XAVIER MARKS PREMIER MALANG - Abdul Choliq; Setiani Setiani (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of organizational culture and work discipline on employee productivity at PT Xavier Marks Premier Malang. This type of research is quantitative with a descriptive approach. The sample used was 57 respondents from a population of 195 people using the Slovin formula. The method used for sampling in this study is non-probability sampling using convenience sampling technique. Data collection technique is to use a questionnaire distributed to the research object. Data analysis technique using smartPLS application. The results showed that the organizational culture variable did not have a significant effect on work productivity with a p-value of 0.102 which is greater than 0.05, while the work discipline variable had a significant positive effect on the work productivity of PT. Xavier Marks Premier Malang employees with a p-value of 0.023 which is smaller than 0.05. So it can be concluded that both have different effects based on the results of the p value of each variable.